The effects of inter-crop cultivation Between rows of citrus crop on spreading of Guignardia citricarpa Ascospores and in the citrus black spot occurrence - Bellotte, José Antonio Miranda; Kupper, Katia Cristina; Rinaldo, Davi [UNESP]; Souza, Andressa de [UNESP]; Goes, Antonio de [UNESP] (Sociedade Brasileira de Fruticultura, 2013)
No presente, foi avaliada a influência do amendoim-forrageiro cv. Amarillis e da gramínea coastcross nas entrelinhas de plantas de laranjeira 'Natal' quanto à produção e liberação de ascósporos de G. citricarpa, e consequente controle da mancha-preta dos frutos cítricos. Os tratamentos avaliados foram: 1- cultivo convencional, sem utilização de fungicidas; 2- cultivo convencional, com utilização de fungicidas; 3- gramínea coastcross, e 4- amendoim forrageiro entre as linhas das plantas. O monitoramento de ascósporos deu-se mediante armadilhas caça-esporos do tipo Quest Volumetric Spore System™. Um total de 33 inspeções foi realizado semanalmente, a partir do final de agosto até início de setembro do ano seguinte. A quantificação da doença deu-se mediante utilização de escala diagramática de notas, sendo também determinada a porcentagem de frutos com padrão comercial. A gramínea coastcross foi o melhor tratamento em reduzir o número de ascósporos liberados, diferindo, estatisticamente, do convencional, porém não dos demais tratamentos. Cultivo intercalar e cultivo convencional associado com aplicações de fungicida foram os mais eficientes quanto à redução da severidade de sintomas da mancha-preta, diferindo do tratamento- -testemunha, sem emprego de fungicida. Esses tratamentos foram os que também proporcionaram a maior porcentagem de frutos com padrão comercial, sendo de 89% a 91%, enquanto no cultivo convencional, sem uso de fungicidas, foi de 73%.

This study highlighted the effect of planting coast-cross grass and forage peanut cv. Amarilis between rows of Natal oranges on spreading of Guignardia citricarpa ascospores and consequent citrus black spot control. Treatments evaluated were: 1- conventional cultivation, free of fungicides; 2- conventional cultivation, using protective fungicides; 3- inter-crop cultivation of coast-cross grass between rows of citrus crops and; 4- inter-cropping cultivation of forage peanut between the rows of citrus crops. Quest Volumetric Spore SystemTM traps were set in order to determine the number of ascospores released. A total of 33 inspections were conducted weekly, from the end of August until early September the following year. A diagrammatic scale was used to determine the severity of the disease as well as the percentage of fruits having a commercial standard. The coast-cross grass was more effective in reducing the number of ascospores produced, whose average statistics were lower than in the conventional treatments, free-fungicides. The inter-crop and conventional cultivation method coupled with fungicide treatment was more effective in reducing the severity of citrus black spot symptoms, and differs statistically from the fungicide-free control method. These methods also resulted in a higher percentage of fruits of a commercial standard, ranging from the 89% through the 91% percentile, and the cultivation, free of fungicides, fell within the 73%.
Efeito de cultivos intercalares nas entrelinhas dos citros na liberação de ascósporos de guignardia citricarpa e na ocorrência da mancha preta dos citros
Keywords: Citrus sinensis; cultural control; Phyllosticta citricarpa; Arachys pintoi; Cynodon dactylon; Citrus sinensis; Controle cultural; Phyllosticta citricarpa; Arachys pintoi; Cynodon dactylon